Multifunctional polymers with interpenetrating structures: luminescence sensing, ECL behaviors, selective detection of Fe3+ ion and rapid removal of anionic dyes. (20th May 2020) - Meng, Lingshu; Zhao, Lun; Guo, Guanlin; Liu, Xin
Abstract : Three unprecedented metal–organic frameworks with interspersed structures have been synthesized and structurally characterized. Abstract : Three novel 3D coordination polymers (CPs), {[Cd(L)(bimb)](H2 O)4 } n (1 ), {[Zn(L)(bibp)](H2 O)(DMF)} n (2 ) and {[Zn(L)(bif)](H2 O)4 } n (3 ) (bimb = 1, 4-bis(imidazoly-1-yl)benzene, bibp = 4, 4′-bis(imidazol-1-yl)biphenyl, bif = 2, 7-bis(1-imidazoly)fluorene, H2 L = 1-(4-carboxylphenyl)piperidine-4-caboxylic acid) have been synthesized under solvothermal conditions. Compound 1 featured a 5-fold interpenetration of the 4-c dia net. Compound 2 and 3 presented a 6-fold interpenetration of the 4-c dia net. Moreover, their luminescence properties and the selective detection of Fe 3+ ion for 1 were investigated. In addition, the adsorption ability of 1 and 2 toward dye molecules was tested, respectively. Furthermore, their ECL behaviors were tested.